Visual factors of aesthetic preferences for mobile phones - Purić, Danka; Mišić, Vladimir (Primenjena psihologija, 2010)
The aim of this study was to examine the effects of certain visual attributes of mobile phones on participants’ aesthetic preferences of the phones. Three factors have been systematically manipulated – the size of the mobile phone, the ratio between its height and its width and the curved versus sharp shape of its borders. 31 participants (with the average age of 25 years) have ranked the phones on the beautiful – ugly continuum. Only the size of the mobile phones has proven to be a significant factor, with participants preferring bigger phones. Asked to explain their criteria of aesthetic preferences and why they’ve rated certain phones as the most and the least beautiful, equal number of participants said that they preferred phones with curved and sharp edges, though phones with extremely curved shape were the least preferred. The simplicity of the phone, the size of its screen and the characteristics of its keyboard were also mentioned as important criteria for aesthetic preferences of our subjects.